Diversity of lactic acid bacteria isolated from fermented mare's milk products based on PCR-RFLP analysis. (February 2019) - Mulyawati, A I; Jatmiko, Y D; Mustafa, I; Ardyati, T; Suharjono,
Abstract: This study aimed to characterize the diversity of lactic acid bacteria (LAB) isolated from fermented mare's milk based on PCR-RFLP. The LAB was isolated from three fermented mare's milk products from three different regions i.e Dompu, Bima, and Sumbawa, Province of West Nusa Tenggara, Indonesia. Fermented milk samples (25 mL) was diluted into 225 mL of saline solution and spread plated onto MRS and M17 agar containing 1 % CaCO3, then incubated at 37 ºC for 48 hours. Single colonies showing a clear zone were randomly selected and purified. The DNA was extracted by the heat-treatment method and amplified using an internal transcribed spacer (ITS) and 5.8S region spacer primers. The amplicons of the 5.8S region spacer were used for restriction fragment length polymorphism (RFLP) analysis using Hae III and Hind III enzymes. The DNA bands were characterized to obtain the LAB clusters. The representative of each LAB cluster was amplified using 16S rDNA primer then sequenced. Total of 41 isolates was grouped into 10 clusters based on the PCR-RFLP analysis. However, only three clusters were identified as LAB from Lactobacillus genus. The Lactobacillus species obtained were L. plantarum and two strains of L. rhamnosus . Four clusters were identified as Staphylococcus genus and three others were Ochrobactrum genus. Thus, the LAB isolates from fermented mare milk obtained were the member of Lactobacillus genus. However, the Gram-negative bacteria and Staphylococcus were still found in the fermented products indicating the poor quality of the products. Therefore, a good manufacturing practice should be implemented during the product preparation.